This preview shows page 1. Sign up to view the full content.
Unformatted text preview: x 2 dx = x = x 1 Z x =0 dy = y ± ± ± x = x 1 x =0 = y ( x 1 ) − y (0) . If we let t be the variable of integration and replace x 1 by x and y (0) by 0, then we can express the solution to the initial value problem as y ( x ) = x Z e t 2 dt. (b) The diFerential equation dy/dx = e x 2 y − 2 separates if we multiply by y 2 and dx . We integrate the separated equation from x = 0 to x = x 1 to obtain x 1 Z e x 2 dx = x 1 Z y 2 dy = 1 3 y 3 ± ± ± x = x 1 x =0 = 1 3 ² y ( x 1 ) 3 − y (0) 3 ³ . 31...
View
Full
Document
This note was uploaded on 03/29/2010 for the course MATH 54257 taught by Professor Hald,oh during the Spring '10 term at Berkeley.
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Equations

Click to edit the document details